PERKEMBANGAN AMAL USAHA MUHAMMADIYAH SIDOARJO 1990-2017 - Imam Ardiansyah; Lailatul Huda (Qurthuba: The Journal of History and Islamic Civilization, 2018)
Abstract: This article examines the development of Muhammadiyah's charitable business in the Krian area of ​​Sidoarjo. The focus of this research is (1) What is the history of the establishment of the Muhammadiyah branch in Krian sub-district (2) What is the role of the chairman of the Muhammadiyah branch in developing Muhammadiyah's charitable business in Krian sub-district (3) What is the history of the development of the Muhammadiyah branch's charitable business in Krian sub-district in 1990-2017 . In this study, the authors used historical research methods, namely heuristics, source criticism, interpretation and historiography. The approach and theoretical framework used to analyze it is from a social science approach to role theory. Role theory explains that the role refers more to function, adjustment and as a process. So, someone occupies a position in society and performs a role. The results of this study found that (1) Muhammadiyah had existed in Krian District since 1937, this happened with the arrival of Mr. Krian was inaugurated in 1966. (2) Within 27 years from 1990 to 2017, the leadership in the Muhammadiyah Branch, to be more precise, had 6 chairmen who served. (3) The development of the charity business of the Muhammadiyah Branch in Krian was fast, especially in the fields of religion, education and health. Keywords: Muhammadiyah, Krian. Business charity